Douleur de hanche fébrile chez un adolescent judoka - Langlais, T.; Morin, C.; Poumellec, M. A.; Ursu, C.; Leonard, J. C. (Science & Sports, 2017)
Introduction: Piriformis syndrome is a frequent pathology in the athlete. Diagnostic delay is often observed.